(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article deals with the return of the Passeio Cantante artistic action to the streets, after two years of social isolation caused by COVID-19, with the aim of leaving a testimony of the experience of the arts of presence and isolation. It adds a narrative about the language that has been created from the intersection between historical heritage, scene and June tradition, which here is called Teatro de Quermesse. To describe how this caipira theater has been made, we add to the information related to Passeio Cantante, information about the urbanization of Campinas since the 18th century, about the people and the June tradition planted here since the 16th century. From the material gathered here, we show how this dramaturgy for alleys, squares and squares is thought of as a scenic event that evokes the memory of the city, from a political perspective of today with a view to proposals for the future. The text dialogues with Leda Maria Martins (1997; 2002), Milton Santos (2014), Luís Antônio Simas (2019), among other references.